(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
Research aims to Know range the human resources development for the electronic management application in the General Traffic Directorate, the research sample, and to clarify the relationship between human resources development variables, such as training management, skills and improving competency for employees, and the application of electronic management, A questionnaire was prepared for the research sample and distributed to a group of administrative and technical staff working in the Traffic Directorate, the research sample to Know range the human resources development in order to apply electronic management without deviations, The research hypothesis came with two main hypotheses: the correlation hypothesis and the impact hypothesis, Through the researcher’s field visit to the Directorate, he found a weakness in developing its human resources, The General Directorate of Traffic is of the important directorates in the country, as the Ministry of Interior relies on it to provide services to citizens, which is witnessing a high demand by citizens, which makes it necessary to think In improving the provision of its services and facing the weakness of the application of electronic management by paying Interest to the human resources development, and this is the research problem. The most important conclusions and recommendations There is a weakness in the training programs provided by the Directorate of the research sample because the Directorate does not prepare training programs to meet the requirements of the workers, so the researcher recommends the need for a strategic planning for the development of human resources and their attachment to the electronic management in the Traffic Directorate, research sample, Increasing the training programs provided by the Directorate to improve the skills and abilities of employees.